Revisiting liquorice (Glycyrrhiza glabra L.) as anti-inflammatory, antivirals and immunomodulators: Potential pharmacological applications with mechanistic insight. - Dheeraj Bisht; Mohmmad Rashid; Rajeshwar Kamal Kant Arya; Deepak Kumar; Sushil Kumar Chaudhary; Vijay Singh Rana; Neeraj K. Sethiya (Elsevier, 2022)
Background: Glycyrrhiza glabra L. (G. glabra) commonly known as liquorice is one of the highly exploited and utilized medicinal plant of the world. Since ancient times liquorice is considered as an auspicious and valuable traditional medicine across the world for treatment of various ailments. Method: Several electronic online scientific databases such as Science Direct, PubMed, Scopus, Scifinder, Google Scholar, online books and reports were assessed for collecting information. All the collected information was classified into different sections to meet the objective of the paper. Results: The electronic database search yielded 3908 articles from different countries. Out of them one ninety-eight articles published between 1956 and 2021 were included, corresponding to all detailed review on G. glabra and research on anti-inflammatories, antivirals and immunomodulatory through pre-clinical and clinical models. From all selective area of studies on G. glabra and its bioactive components it was established (including molecular mechanisms) as a suitable remedy as per the current requirement of pandemic situation arise through respiratory tract infection. Conclusion: Different relevant studies have been thoroughly reviewed to gain an insight on utility of liquorice and its bioactive constituents for anti-inflammatories, antivirals and immunomodulatory effects with special emphasized for prevention and treatment of COVID-19 infection with possible mechanism of action at molecular level. Proposed directions for future research are also outlined to encourage researchers to find out various mechanistic targets and useful value added products of liquorice in future investigations.